Analisis Strategi Komuniasi Jurnalis Perempuan dalam Peliputan Kasus Kekerasan Seksual - Achmad Basofi; Farida Hariyati; Indriani Indriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study addresses an analysis of the communication strategies employed by female journalists in the context of reporting on cases of sexual violence. In this research, the method employed is a descriptive qualitative approach, enabling an in-depth investigation into observable behaviors of the research subjects. The findings highlight the crucial role of female journalists in bringing often overlooked issues to public attention. They not only serve as conveyors of information but also as advocates for social change. The communication strategies they employ include sensitive and empathetic approaches to victims, maintaining integrity in case reporting, and utilizing emotional intelligence to capture the nuances of victims' experiences. However, female journalists also face a range of complex challenges, including external pressures, societal stigma, and limitations in accessing information and sources. Nonetheless, their courage and steadfastness in advocating for victims' rights and raising often neglected issues remain unwavering. This study makes a significant contribution to expanding understanding of the roles and challenges faced by female journalists in reporting on cases of sexual violence, while emphasizing the importance of sensitive and empathetic communication strategies in addressing socially sensitive issues.